Bilateral ultrasound-guided thoracic erector spinae plane blocks using a programmed intermittent bolus improve opioid-sparing postoperative analgesia in pediatric patients after open cardiac surgery: a randomized, double-blind, placebo-controlled trial. Issue 10 (19th October 2020) - Macaire, Philippe; Ho, Nga; Nguyen, Vien; Phan Van, Hieu; Dinh Nguyen Thien, Kim; Bringuier, Sophie; Capdevila, Xavier
Abstract : Background: Postoperative pain after pediatric cardiac surgery is usually treated with intravenous opioids. Recently, the focus has been on postoperative regional analgesia with the introduction of ultrasound-guided erector spinae plane blocks (ESPBs). We hypothesized that bilateral ESPB with a programmed intermittent bolus (PIB) regimen decreases postoperative morphine consumption at 48 hours and improves analgesia in children who undergo cardiac surgery. Methods: This randomized, double-blind, placebo-controlled study comprised 50 children who underwent cardiac surgery through midline sternotomy. The patients were allocated randomly into two groups: ultrasound-guided bilateral ESPB at the level of T3–T4 transverse process then PIB with saline infusion (group 1, n=23) or PIB with 0.2% ropivacaine (group 2, n=27). Intravenous morphine at 30 µg/kg/hour was used as rescue analgesia. Postoperative pain was assessed using the COMFORT-B score for extubation, drain removal, and mobilization, and the FLACC (Face, Legs, Activity, Cry, Consolability) scale at 0, 2, 4, 6, 8, 12, 16, 20, 24, 36, and 48 hours after surgery. Adverse events were noted. Results: The total dose of morphine in 48 hours was significantly decreased in patients receiving a bilateral ESPB with ropivacaine (120±320 µg/kg) compared with patients with saline infusion (512±560 µg/kg; p=0.03). Fourteen per cent of patients required rescue analgesia with morphine in group 2 compared with 41% in group 1 (p=0.05). The patients in group 2 demonstrated significantly reduced COMFORT-B scores at extubation, drain removal, and mobilization compared with those in group 1 and had reduced FLACC scale levels at 20 and 24 hours postoperatively (p=0.05 and p=0.001, respectively). No differences were reported for extubation and drain removal times or for length of hospital stay. In addition, vomiting episodes were decreased in group 2 (p=0.01). Conclusions: In pediatric cardiac surgery, the results of this study confirm our hypothesis that bilateral ESPB analgesia with ropivacaine decreases the postoperative morphine consumption at 48 hours and demonstrates better postoperative analgesia compared with a control group. Trial registration number NCT03593642.